Domestic definitions of personality and personological thinking of psychologists and educators as a factor of young people’s socialization - Rybalka, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
There are provided scientific definitions of personality that were created in the period from the second half of the XIX to the XXI century by national philosophers, psychologists, educators. Orthonomic, content-frequent and antinomic analysis of their content is held to create personological thinking of psychologists and teachers to improve the socialization of young people .